Soil Nailing Design By Using Geo 5 Program - Wardani, Sri Ardiyati Kusuma, Anto Budi Listyawan ST. M.Sc (2017)
Indonesia has many mountainous area, slope and hills and it often used as residents, resorts, hotels, and highway as infrastructure. However many slopes is unstable, therefore should be a reinforcement on slope to overcome the problem of landslides, and it is soil nail wall. To make easy when design soil nail wall, it needed the assistive program. Based on this problem, the writer want to investigate the usage of program in designing soil nail wall, the program is Geo 5. In this research data is taken from Piyungan road-the boarder of Gunung Kidul. Soil nail wall that consist of nail bar and grout, controlling the internal stability (nail pull-out failure and nail tensile failure) and external stability (global stability, sliding, bearing capacity), weight of soil (γ) 15.186 kN/m3; specific gravity (G_s) 2.66; cohesion (c) 15.984 kN/m2; and friction angle (ϕ) 30.440. Geology condition of soil layer in investigation location is dominated by sand. Calculation done by manual calculation and Geo 5 program. After the calculation, the result is Global stability (FSG) is 2.42 (manual) and 2.43 (Geo 5) > 1.5(safe).Sliding stability (FSSL) is 3.53 (manual) and 8.29 (Geo 5) > 1.5(safe).Bearing capacity (FSH) is 12.85 (manual) and 8.57 (Geo 5) > 3.0 (safe). Nail tensile failure (FST) is 3.04 (manual) and nail pull out resistance (FSP) is 6.37 (manual) and internal stability is 3.21 (Geo 5) > 2.0 (safe). The differences result between manual calculation and Geo 5 program are caused by differences of equation and method that have been used. In manual calculation is using Rankine and in Geo 5 program using Coulomb and Caqout- Kerisel. And also because of manual calculation ignoring the calculation of grout and concrete cover. Keywords: geo5 program, soil nailing, slope stability, nailed slope